Industrial training report: University of Malaya Library / Siti Aisyah Mat Daud - Mat Daud, Siti Aisyah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
To complete my studying as final year's student, I have finished industrial training at University of Malaya Library, University of Malaya, Kuala Lumpur for five months from August to December. I have trained at Central Library for one months and Education Library for four months. This industrial training report contains introduction to University of Malaya Library and Education Library as my industrial training place, all my industrial training activities at University of Malaya Central Library and Education Library, and special projects that I have conducted during my industrial training period. Besides that, I also have explain about how application of knowledge, skills and experience in undertaking the task, my personal thought and opinion about industrial training and also what limitations that I have during my industrial training's period and recommendation to overcome those barriers.